The Heritage of Tolstoy’s Artistic Detail in the Poetics of Chekhov (Defamiliarization and „Randomness”) - Zoltán, Dominika (Slavica, 2021)
One type of the “random Chekhovian detail ”can be referred to as a special cognitive phenomenon arising during the perception of the background and foreground within the depicted perception of the hero. In this paper, I suggest that this technique works if we perceive Chekhov’s laconicity against the detailed descriptions of the inner world of Tolstoy’s characters in the process of their estrangement. In the first part using the example of “War and Peace” I examine the “random” details concerning various features of Tolstoy’s defamiliarization and show their transformation in Chekhov’s poetics. The examples from Chekhov’s early short stories “Grisha” and “Polinka” demonstrate an intermediate level of this transformation. In the second part I turn to the story “The Lady with the Dog” and consider the transformation of Tolstoy’s technique through parallels with the novels “War and Peace” and “Anna Karenina”. The situation of Gurov and Tolstoy’s characters (Natasha, Prince Andrei, Levin) is similar with regard to the fact that they retain true love in their hearts and get into an everyday social situation, where they are exposed to the the automatism and lies of everyday life with special intensity.